PELAKSANAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI TINGKAT SEKOLAH MENENGAH ATAS - Yayat Hidayatulloh; Uus Ruswandi (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to explain abaout the implementation of learning activities in Islamic Religious Education and Morals in Senior High Schools (SMA), related to objectives, learning materials, methods used, and evaluation implementation. The type of research is a type of qualitative research using the literature study method. The results of the study indicate that the implementation of Islamic Religious Education and Moral carried: 1) Instilling the Islamic faith through activities of developing knowledge, appreciation, practice, habituation, and experience for students about Islamic teachings so that from these activities they can become human beings with character, faith and piety; 2). Realizing Indonesian people who are religiously obedient and have noble character, namely humans who are knowledgeable, diligent in worship, intelligent, productive, honest, fair, ethical, disciplined, tolerant (tasamuh), maintain personal and social harmony and develop religious culture in the school community. To achieve this goal, of course, one must use the right method, including lectures, discussions, questions and answers, and problem solving. To achieve the learning objectives of Islamic Religious Education and Character Education in Senior High Schools (SMA) through evaluation, both through tests and non-tests. Keyword: Learning, PAI, high school